The evaluation of a novel technique to treat saphenous vein incompetence: preclinical animal study to examine safety and efficacy of a new vein occlusion device. (February 2014) - Farber, A; Belenky, A; Malikova, M; Brenner, O; Brandeis, Z; Migdal, M; Orron, D; Kim, D
Objectives: We tested a novel technique to treat great saphenous vein (GSV) incompetence in an animal model. Methods: V-block (VVT Medical Ltd, Kfar Saba, Israel), an occlusion device composed of a nitinol frame and anchoring hooks, was percutaneously deployed at the saphenofemoral junction in 12 sheep. Four of the 12 sheep were treated with adjunctive liquid sclerotherapy. Animals underwent duplex ultrasound, venography and histopathological evaluation immediately postimplantation at 30, 60 and 90 days. Results: V-block was successfully deployed in all animals without adverse events. There was no device migration at follow-up. Histopathological analysis demonstrated V-block to be lodged within the GSV and surrounded by fibrous tissue in all samples. Obliteration of the GSV lumen, widespread intimal loss and multifocal medial smooth muscle loss was noted. Conclusions: In this animal study V-block was deployed without complications, remained in stable position and led to GSV occlusion. This device has promise for future use in humans.